Structure and composition of mixed surfactant micelles of sodium dodecyl sulfate and hexaethylene glycol monododecyl ether and of hexadecyltrimethylammonium bromide and hexaethylene glycol monododecyl ether - Penfold, J; Staples, E; Thompson, L; Tucker, I; Hines, J; Thomas, R; Lu, JR; Warren, N (1999)
Small-angle neutron scattering has been used to study the structure and composition of mixed ionic-nonionic surfactant micelles. A comparison between two different mixed surfactant systems, sodium dodecyl sulfate (SDS) and hexaethylene glycol monododecyl ether (C12EO6) and hexadecyltrimethylammonium bromide (C16TAB) and C12EO6, both in 0.1 M NaCl, has been made. In the latter system, ideal mixing is observed, and in the former, departure from ideality, broadly consistent with regular solution theory, RST, is observed. The deviations from the predictions of RST are attributed to subtle changes in the packing of the two surfactants in the mixed micelles. For the SDS/C12EO6 mixture, the micellar aggregation number is essentially constant with composition and concentration, whereas for the C16TAB/C12EO6 mixture there is a marked micellar growth with increasing concentration and mole fraction of C12EO6 in solution. The SANS results on structure and composition are compared with the results reported for other mixed surfactant systems and are discussed in the context of recent theoretical developments. © 1999 American Chemical Society.